Social Network Analysis and the Dynamics of Love in Early Modern Drama - Digitally Visualising Love Interactions in the Works of William Shakespeare - Nash, Louise (Trinity College (Dublin, Ireland). School of Languages, Literature and Cultural Studies, 2021)
This thesis combines the fields of social network analysis and early modern drama in order to gain new perspectives on the dynamics of love-based interactions in the works of English playwright William Shakespeare. Using the seminal text of American sociologist Linton C. Freeman, The Development of Social Network Analysis, the four features of modern social network analysis are defined in the context of modern advancements in the field and the yet-fully represented contributions of the humanities. The thesis then seeks to devise a social network analysis project of its own, investigating the frequency of 'love' interactions and their prevalence among genders across the Shakespearean works. The products of this project are several social network visualisations that depict the social dynamics of this love-based behaviour. The visualisations demonstrate several key trends among Shakespeare's most prominent ‘love’ texts, namely the disproportionate frequency of male-to-male interactions, gender clustering, female group size and more. This study partially reinforces existing work relating social dynamics depicted in Shakespeare to real-world social groups but also contributes methodologies related to the extraction of keyword data and subsequent visualisation. Keywords: William Shakespeare, early modern drama, social network analysis, love, digital humanities, keyword extraction, network visualisation, structural perspective
Keywords: Digital Humanities and Culture